Differences In Oxygen-Dependent Nitric Oxide Metabolism By Cytoglobin And Myoglobin Account For Their Differing Functional Roles - Liu, Xiaoping (2013)
The endogenous vasodilator nitric oxide (NO) is metabolized in tissues in an O(2)-dependent manner. In skeletal and cardiac muscle, high concentrations of myoglobin (Mb) function as a potent NO scavenger. However, Mb concentration is very low in vascular smooth muscle where low concentrations of cytoglobin (Cygb) may play a major role in metabolizing NO. Questions remain regarding how low concentrations of Cygb and Mb differ in their NO metabolism and the basis for their different cellular roles and functions. In this study, electrode techniques were applied to perform comparative measurements of the kinetics of NO consumption by Mb and Cygb. UV/Vis spectroscopic methods and computer simulations were performed to study the reaction of Mb and Cygb with ascorbate (Asc) and the underlying mechanism. It was observed that the initial rate of Cygb(3+) reduction by Asc was 415-fold greater than that of Mb(3+). In the low [O(2)] range (0-50 μM), Cygb-mediated NO consumption rate is ~500 times more sensitive to changes in O(2) concentration than that of Mb. The reduction of Cygb(3+) by Asc follows a reversible kinetic model while its reduction of Mb(3+) is irreversible. A reaction mechanism for Cygb(3+) reduction by Asc was proposed and the reaction equilibrium constants determined. Our results suggest that the rapid reduction of Cygb by cellular reductants enables Cygb to efficiently regulate NO metabolism in the vascular wall in an oxygen-dependent manner, while the slow rate of Mb reduction does not provide this oxygen dependence.